Paleoproterozoic mafic dyke from Kongling terrain in the Yangtze Craton and its implication - Peng, Min; Wu, YuanBao; Wang, Jing; Jiao, WenFang; Liu, XiaoChi; Yang, SaiHong (Chinese science bulletin, 2009)
Mafic dyke is a sign of regional extension, and thus has important tectonic significance. A great amount of mafic dykes occur in the Kongling terrain of the Yangtze Craton, which have great bearing on the early evolution of the Yangtze Craton. Their ages, however, have not been well constrained. In this paper we report an integrated study of zircon U-Pb age and Hf isotope compositions for a mafic dyke in the Kongling terrain. The zircons yielded a weighted mean 207 Pb/ 206 Pb age of 1852±11Ma, which represents its intrusion age. They have ɛ Hf ( t ) values of −6.3 to 0.5, with a weighted mean of −3.06±0.88, suggesting that the mafic dyke came from metasomatic mantle. The results indicate that the Yangtze Block had transformed into post-collisional extensional regime at ca. 1850 Ma. In the same period, the Yangtze Craton shows enough rigidity to produce brittle rupture, and thus has the characteristics of a craton.